Immunosuppression in Experimental Chagas Disease Is Mediated by an Alteration of Bone Marrow Stromal Cell Function During the Acute Phase of Infection - Müller, Uwe; Schaub, Günter A.; Mossmann, Horst; Köhler, Gabriele; Carsetti, Rita; Hölscher, Christoph (Frontiers in Immunology, 2018)
After infection with Trypanosoma cruzi (T. cruzi), the etiologic agent of Chagas disease, immunosuppression and apoptosis of mature lymphocytes contribute to the establishment of the parasite in the host and thereby to persistence and pathology in the chronic stage of infection. In a systemic mouse model of experimental Chagas disease, we have demonstrated a strong depletion of mature B cells in the spleen during the first two weeks of infection. Remarkably, the decrease in this cell population commences already in the bone marrow from infected mice and is a concomitant of an increased apoptosis in pro- and pre-B cell populations. Pro- and pre-B cells in the bone marrow show a significant reduction accompanied by a functional disturbance of bone marrow-derived stromal cells resulting in diminished levels of IL-7, an essential factor for the development of B cell precursors. Ex vivo, stromal cells isolated from the bone marrow of infected mice have a strikingly impaired capacity to maintain the development of pro- and pre-B cells obtained from uninfected animals. Together, the reduction of an active humoral immune response during acute Chagas disease suggests to be an initial immune evasion mechanism of the parasite to establish persistent infection. Therefore, prevention of B cell depletion by rescuing the stromal cells during this early phase, could give rise to new therapeutic approaches.